A livelihood intervention to reduce the stigma of HIV in rural Kenya: longitudinal qualitative study - Tsai, Alexander C. (AIDS Behav, 2017)
The scale-up of effective treatment has partially reduced the stigma attached to HIV, but HIV still remains highly stigmatized throughout sub-Saharan Africa. Most studies of anti-HIV stigma interventions have employed psycho-educational strategies such as information provision, counseling, and testimonials, but these have had varying degrees of success. Theory suggests that livelihood interventions could potentially reduce stigma by weakening the instrumental and symbolic associations between HIV and premature morbidity, economic incapacity, and death, but this hypothesis has not been directly examined. We conducted a longitudinal qualitative study among 54 persons with HIV participating in a 12-month randomized controlled trial of a livelihood intervention in rural Kenya. Our study design permitted assessment of changes over time in the perspectives of treatment-arm participants (N=45), as well as an understanding of the experiences of control arm participants (N=9, interviewed only at follow-up). Initially, participants felt ashamed of their seropositivity and were socially isolated (internalized stigma). They also described how others in the community discriminated against them, labeled them as being “already dead,” and deemed them useless and unworthy of social investment (perceived and enacted stigma). At follow-up, participants in the treatment arm described less stigma and voiced positive changes in confidence and self-esteem. Concurrently, they observed that other community members perceived them as active, economically productive, and contributing citizens. Participants in the control arm described continued stigma with none of these changes. In summary, our findings suggest a theory of stigma reduction: livelihood interventions may reduce internalized stigma among persons with HIV and also, by targeting core drivers of negative attitudes toward persons with HIV, positively change attitudes toward persons with HIV held by others. Further research is needed to formally test these hypotheses, assess the extent to which these changes endure over the long term, and determine whether this class of interventions can be implemented at scale.